Efficient quantum private queries based on quantum key distribution with pulse-position modulation. (26th March 2019) - Lai, Hong; Luo, Mingxing; Xu, Yongjian; Pieprzyk, Josef; Pan, Lei; Zhang, Jun; Orgun, Mehmet A
Abstract: Up to now, there are only a few studies on the application of pulse position modulation (PPM) and orbital angular momentum (OAM) in measurement-device-independent (MDI) quantum private queries (QPQ) protocols. Given this, we design a QPQ protocol based on PPM-OAM and MDI-QKD (quantum key distribution), i.e. PPM-OAM-MDI-QPQ protocol, which avoids the dependence of the basis besides inheriting the advantages of MDI-QPQ. Our PPM-OAM-MDI-QPQ protocol can achieve longer-distance QPQ and speed up private queries. Moreover, our PPM-OAM-MDI-QPQ protocol can eliminate the basis-dependent flaw and demonstrate a useful technique for high-rate satellite-based QPQ. Meanwhile, our protocol applies quantum memory to achieve the function of a quantum repeater, achieving much longer-distance QPQ.